Perioperative Neutrophil-to-Lymphocyte Ratio as an Independent Predictor of Acute Kidney Injury Following Cardiac Surgery: A Multicenter Observational Study - Chaiyasit , Anan; Wattanakul, Siriporn; Rattanapong , Kittisak (Journal of Society Medicine, 2026)
Introduction: Cardiac surgery-associated acute kidney injury (CSA-AKI) is a frequent and severe complication that significantly contributes to postoperative morbidity and mortality. Systemic inflammation plays a central role in the pathophysiology of CSA-AKI, and the neutrophil-to-lymphocyte ratio (NLR), a simple and widely available biomarker, has shown potential as a prognostic tool for CSA-AKI. However, robust multicenter evidence regarding its perioperative role in predicting CSA-AKI remains limited. Methods: We conducted a multicenter observational cohort study involving 1,248 adult patients who underwent cardiac surgery. NLR was measured at three critical time points: preoperatively, upon ICU admission, and on the first postoperative day. The primary outcome was CSA-AKI, as defined by the Kidney Disease: Improving Global Outcomes criteria. Multivariable mixed-effects logistic regression models were used to assess the independent association between perioperative NLR and CSA-AKI, adjusting for relevant confounders and center-level variability. Model performance was evaluated using discrimination and calibration metrics. Results: CSA-AKI occurred in 27.6% of the patients. Elevated perioperative NLR was significantly associated with an increased risk of CSA-AKI. In the adjusted analyses, higher preoperative NLR independently predicted CSA-AKI (adjusted OR 1.82 per unit increase; 95% CI 1.34–2.47). Similar associations were observed between ICU admission and postoperative NLR. Incorporating NLR into the predictive model enhanced its discrimination (AUC 0.78) and demonstrated a strong calibration. Conclusion: Perioperative NLR is an independent and clinically significant predictor of CSA-AKI. Its simplicity, cost-effectiveness, and accessibility make it an invaluable tool for early risk stratification in patients undergoing cardiac surgery. Integrating NLR into perioperative assessment models could facilitate personalized preventive strategies, potentially improving clinical outcomes, and guiding more targeted interventions for CSA-AKI.